Membrane topologies of PEX13 and PEX14 provide new insights on the mechanism of protein import into peroxisomes. (28th November 2018) - Barros‐Barbosa, Aurora; Ferreira, Maria J.; Rodrigues, Tony A.; Pedrosa, Ana G.; Grou, Cláudia P.; Pinto, Manuel P.; Fransen, Marc; Francisco, Tânia; Azevedo, Jorge E.
Abstract : PEX13 and PEX14 are two core components of the so‐called peroxisomal docking/translocation module, the transmembrane hydrophilic channel through which newly synthesized peroxisomal proteins are translocated into the organelle matrix. The two proteins interact with each other and with PEX5, the peroxisomal matrix protein shuttling receptor, through relatively well characterized domains. However, the topologies of these membrane proteins are still poorly defined. Here, we subjected proteoliposomes containing PEX13 or PEX14 and purified rat liver peroxisomes to protease‐protection assays and analyzed the protected protein fragments by mass spectrometry, Edman degradation and western blotting using antibodies directed to specific domains of the proteins. Our results indicate that PEX14 is a bona fide intrinsic membrane protein with a Nin ‐Cout topology, and that PEX13 adopts a Nout ‐Cin topology, thus exposing its carboxy‐terminal Src homology 3 [SH3] domain into the organelle matrix. These results reconcile several enigmatic findings previously reported on PEX13 and PEX14 and provide new insights into the organization of the peroxisomal protein import machinery. Enzymes: Trypsin, EC3.4.21.4 ; Proteinase K, EC3.4.21.64 ; Tobacco etch virus protease, EC3.4.22.44 . Abstract : Defining the membrane topologies of PEX13 and PEX14, two core components of the peroxisomal protein translocon, is crucial to understand the peroxisomal protein import machinery. We show that PEX14 is an intrinsic membrane protein with an N terminusin ‐C terminusout (Nin ‐Cout ) topology, and that PEX13 adopts an Nout ‐Cin topology. These results explain several enigmatic findings previously reported and provide new insights on the mechanism of this machinery.